1995
DOI: 10.1007/bf00261272
|View full text |Cite
|
Sign up to set email alerts
|

Swallowing therapy of neurologic patients: Correlation of outcome with pretreatment variables and therapeutic methods

Abstract: The results of swallowing therapy in 58 patients with neurologic disorders are presented. All patients received tube feeding, either partially or exclusively, at admission, and successful outcomes, defined as exclusively oral feeding, were achieved in 67% of patients over a median treatment interval of 15 weeks. A subset of 11 patients who had experienced disease onset 25 weeks or more prior to admission nonetheless had a similar success rate of 64%. No other pretreatment variable, including age, localization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
39
0
11

Year Published

1998
1998
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(54 citation statements)
references
References 11 publications
4
39
0
11
Order By: Relevance
“…These findings were supported in an additional study by Neumann et al [15] in which the outcome of treatment on 58 patients who were on nonoral feedings secondary to neurologic disease was presented. For this study, the median time postonset was 10 weeks, with a range of 3-156 weeks.…”
supporting
confidence: 76%
See 1 more Smart Citation
“…These findings were supported in an additional study by Neumann et al [15] in which the outcome of treatment on 58 patients who were on nonoral feedings secondary to neurologic disease was presented. For this study, the median time postonset was 10 weeks, with a range of 3-156 weeks.…”
supporting
confidence: 76%
“…Neumann and colleagues published a series of papers reporting on the efficacy of intervention in a large group of patients with dysphagia of neurogenic origin [14][15][16]. The initial study [14] reported on a group of 66 patients with dysphagia subsequent to a broad range of neurologic etiologies, including brainstem and cortical stroke, tumor, trauma, Parkinson's disease, amyotrophic lateral sclerosis (ALS), and cerebellar ataxia.…”
mentioning
confidence: 99%
“…This step is critical when focusing on intervention programs to reduce the incidence of pneumonia, as clinical outcomes will be more effective if we target the most important risk factors in all critical areas. A few studies have applied specific treatments such as swallowing therapy [52][53][54][55][56], but with mixed results, perhaps because other risk factors were not addressed.…”
mentioning
confidence: 99%
“…Other scales use too few severity, as presented. Separation by severity was initially chosen and has remained over a 5-year period for the categories [20,34,36], such as the presence or absence of aspiration or a feeding tube. Narrow-perspective scales following reasons.…”
Section: Discussionmentioning
confidence: 99%